2023
DOI: 10.1101/2023.02.06.527276
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insulin signaling regulatesPink1mRNA localization via modulation of AMPK activity to support PINK1 function in neurons

Abstract: Mitochondrial quality control failure is frequently observed in neurodegenerative diseases. The detection of damaged mitochondria by stabilization of PTEN-induced kinase 1 (PINK1) requires transport of Pink1 mRNA by tethering it to the mitochondrial surface. Here, we report that inhibition of AMPK by activation of the insulin signaling cascade prevents Pink1 mRNA binding to mitochondria. Mechanistically, AMPK phosphorylates the RNA anchor complex subunit SYNJ2BP within its PDZ domain, a phosphorylation site th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…Treatment with the AMPK Activator AICAR had little effect (Fig. 1E-H, consistent with already high AMPK activity in the imaging medium lacking insulin (14). The effect of CC was not due to altered PINK1 processing (Fig.…”
Section: Visualization and Regulation Of Pink1 Translationsupporting
confidence: 72%
See 2 more Smart Citations
“…Treatment with the AMPK Activator AICAR had little effect (Fig. 1E-H, consistent with already high AMPK activity in the imaging medium lacking insulin (14). The effect of CC was not due to altered PINK1 processing (Fig.…”
Section: Visualization and Regulation Of Pink1 Translationsupporting
confidence: 72%
“…Instead, mechanisms anchoring the ribosome and/or mRNAs to the mitochondrion have been described, which rather support cotranslational import (31)(32)(33). However, constant mitochondrial association of Pink1 mRNA prevents PINK1 function in neurons (14), arguing that the mRNA needs to be untethered to produce a fully functional protein. Untethering of Pink1 mRNA might be a prerequisite for mitophagy as it increases the cytosolic dwell time and potentially inhibits co-translational import of the PINK1 precursor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, protein phosphorylation may regulate the localization and translation of mitochondria-associated transcripts. PKA-mediated phosphorylation of AKAP1 increases its binding affinity as mentioned above, and we have recently observed that the master metabolic regulator AMP-activated protein kinase (AMPK) phosphorylates SYNJ2BP [ 129 ]. This phosphorylation is necessary for efficient recruitment of its RNA-binding partner SYNJ2 and thereby regulates the localization of Pink1 mRNA.…”
Section: Local Translation Supports the Pink1-mediated Mitochondrial ...mentioning
confidence: 99%
“…Previous studies have shown that, like MFN2 and VDAC1, SYNJ2BP is a Parkin substrate [ 174 , 175 ], suggesting that not only will the MERCS mediated by SYNJ2BP and RRBP1 be released upon Parkin activation, but also the tethering of the Pink1 mRNA could be diminished. Evidence from our lab suggests that release of the Pink1 mRNA from SYNJ2BP and mitochondria stimulates PINK1 production and, thereby, promotes mitophagy [ 180 ].…”
Section: Crosstalk Between Mitophagy and Mercsmentioning
confidence: 99%